Economic thought, foundational problems of mainstream economics and the alternative of Islamic Economics - Omercic, Jasmin; Mohamed Haneef, Mohamed Aslam; Mohammed, Mustafa Omar (Universitas Muhammadiyah Yogyakarta, 2020)
Economic thought always permeated human living. Economic thought and the development of economics as a discipline in the last few centuries made it central to the world order. However, the foundational problems that mainstream economics suffers from led to uncounted crises and issues within the same order that created it. A physicalist ontology, rationalist epistemology, axiological futility and methodological deficiency are the problems of philosophical foundations of mainstream economics we reviewed in this paper. The methodology of this paper is qualitative and generally adopts the library research and critical content analysis methods to review and respond to identified foundational problems. Muslims islah and tajdid responses to the West and mainstream economics problems and issues found shape in Islamisation of Knowledge (IOK) and Islamic Economics (IE). The recent shift to Integration of Knowledge (IoK) universalizes the appeal and revives the zeal for IE development in light of IoK based on IOK in this paper. A thorough analysis of IOK, IoK and IE responses to the West and mainstream economics enabled us to appraise it as the alternative and solution to the foundational problems. The paper clarified the way for future research in IE in light of IoK and directed the practitioners and regulators towards economic reasoning based on robust foundations.